Analysis of lora communication reliability using gnu radio in simulated LEO satellite channels - Muhammad Fathi Irfan; Herwin Melyanus Hutapea; Maulana Ali Arifin; Achmad Darwin (International Enterprise Integration Association, 2026)
Low Earth Orbit (LEO) satellite communication using LoRa modulation faces persistent challenges including Doppler frequency shifts, free-space path loss, and synchronization instability that limit communication reliability for satellite-based Internet of Things (IoT) applications. Although LoRa has been widely adopted for terrestrial long-range communication, systematic Software-Defined Radio (SDR) evaluations of LoRa under LEO-like channel impairments remain scarce, particularly studies that simultaneously analyze multiple performance indicators across a complete Spreading Factor (SF) range. This study addresses that gap by proposing a reproducible GNU Radio-based SDR simulation framework that integrates LEO channel impairments (Doppler shift, free-space path loss, and atmospheric attenuation) and simultaneously evaluates Bit Error Rate (BER), Signal-to-Noise Ratio (SNR), and Time on Air (ToA) for 24 SF–CR configurations (SF7–SF12 × CR4/5–CR4/8) at a fixed bandwidth of 125 kHz. The novelty of this work lies in the joint multi-metric SDR assessment of LoRa under satellite-like impairments and the identification of practical SF–CR operating points that balance reliability and efficiency for prospective LEO deployments. The results show that SF7 with CR4/6 and CR4/7 yields the most stable performance, achieving BER as low as 0.01, SNR around −8 to −9 dB, and ToA below 0.03 s, while configurations at SF11–SF12 exhibit severe BER degradation (≥ 0.86) and ToA up to 1.85 s due to synchronization sensitivity under Doppler-affected conditions. These findings provide quantitative guidance for parameter selection in LoRa-based LEO communication systems, particularly the RIDU-Sat development program in Indonesia.